Dialogue - Mentzer, Marc S.; Weaver, Gary R.; Agle, Bradley (Academy of Management Review, 2002)
The article discusses the 2002 article “Religiosity and Ethical Behavior in Organizations: A Symbolic Interactionist Perspective,” by G.R. Weaver and B.R. Agle, and offers a rebuttal to the commentary by the authors Weaver and Agle. The commentary criticizes the suggestion of Weaver and Agle that employees should be more public in communicating their religious affiliation to colleagues. Weaver and Agle respond that the author did not consider the complexity of the relationship between religion and management thoroughly enough before asserting his opinion.